Density Functional Study on the Structural, Frontier Orbital, Electronic, and Magnetic Properties of the Transitional Metal Clusters $Pd_5(CO)_n$ $(n=1$ to $6)$ (Journal of Atomic and Molecular Sciences, 2013)
The generalized gradient approximation based on density functional theory is used to analyze the structural, electronic, and magnetic properties of the transition metal clusters $Pd_5(CO)_n$ $(n=1$ to $6).$ For $Pd_5CO,$ the most stable isomer is the singlet state structure with $C$ atom adsorbed on the hollow site in the form of $CO$ molecule, as same as the conclusion reported by Zanti et al (Eur. J. Inorg. Chem. 2009, 3904). In the most stable isomers of $Pd_5(CO)_2$ and $Pd_5(CO)_3,$ the first $CO$ molecule is adsorbed on the hollow site, while the second and the third $CO$ molecules are adsorbed on the bridge sites, whereas, for the most stable $Pd_5(CO)_n$ $(n=4,5,6),$ all $CO$ molecules are adsorbed on the bridge sites. It is known from the adsorption energy that $Pd_5(CO)_2$ should be the most possible adsorption product. The energy gap indicates that $Pd_5(CO)_n$ $(n=1$ to $6)$ have the enhanced dynamical stability compared to $Pd_5$, and $Pd_5(CO)_3$ should be most dynamically stable of all. The chemisorptions of $CO$ molecules onto the $Pd_5$ cluster are non-dissociative and the strength of $C-O$ bond becomes weaker while more $CO$ molecules are adsorbed. Along with the increase of the $CO$ molecules in $Pd_5(CO)_n$ $(n=1$ to $6),$ the ability for detaching electrons is weakened and that for obtaining electrons is improved. The magnetic moment of $Pd_5$ is $2μ_B,$ however, $Pd_5(CO)_n$ $(n=1$ to $6)$ have no magnetic moment.